Challenges of allergic diseases in the Qassim Region of Saudi Arabia: A call for comprehensive prevention and control strategies - Kundi, Ghulam Muhammad (International Journal of Health Sciences, 2024)
Allergic diseases have become a significant concern for public health globally and the Qassim region in Saudi Arabia is no exception.[1] With a population, exceeding 1.3 million, the Qassim is known for its climate agricultural activities and rapid urbanization all of which play a role in the complexity of allergic disease prevalence.[2] Allergic rhinitis asthma and atopic dermatitis are among the most prevalent allergic disorders influencing individuals across all age groups leading to considerable morbidity and a decline in quality of life.[3] The rising prevalence of these conditions highlights the importance of understanding the challenges faced in Qassim and establishing effective prevention and control measures. Allergies often manifest as reactions on the skin triggered by certain foods, insect stings, or medications causing issues like eczema or hives. The second type is Anaphylaxis which is a severe allergic reaction that can be life threatening and requires immediate medical assistance.[4] These chronic allergies can affect quality of life in ways such as disrupting sleep causing fatigue and reducing productivity. Moreover, managing allergies can place a burden on families and health-care systems due to expenses and lost productivity.[5] In addition, respiratory allergies, to pollen and dust mites, can worsen asthma and other respiratory issues.[6] In the Qassim region similar to many areas, common allergies include (1) Pollen allergies prevalent during spring when plants bloom, (2) dust mite allergies often worsened by indoor settings, (3) food allergies, such as reactions to nuts, dairy, or seafood, (4) insect allergies caused by stings from bees or wasps, and (5) allergies to medications reactions to medications, especially in the elderly. Statistics show that 25% of children and young adults have pollen allergies leading to symptoms like sneezing and itchy eyes with a peak during spring. In addition, 18% of adults aged 30–50 are affected by dust mite allergies causing coughing and nasal congestion although this rate has remained steady over the past year. Moreover, 12% of children under 12 show signs of food allergies such as hives and swelling with an upward trend. Similarly, 7% of individuals across all age groups experience insect allergies resulting in anaphylaxis and rashes while 10% of older adults aged 50 and above have drug allergies that manifest as skin reactions and nausea with a noteworthy increase.